A modified erythropoietin bioassay using protein deprived mice - Fırat, D.; Haber, C. (The Turkish Journal of Pediatrics, 1972)
A modified erythropoietin bio-assay using protein deprived CFI adult female mice is described. After 4 days of protein deprivation, the assay is capable of detecting 0.02 units of Step III sheep erythropoietin as measured by per cent increases in Fe59 incorporation into circulating RBC of mice in 48 hours.The specificity of the method is demonstrated by suppression of the effect of erythropoietin or plasma by simultaneous injections of anti-erythropoietin.